Antara Kebebasan dan Penodaan Agama: Menimbang Proyek “Jalan Tengah” Mahkamah Konstitusi RI tentang UU Penodaan Agama - Rumadi Rumadi (JURNAL INDO-ISLAMIKA, 2012)
This paper attempts to examine to what extent the verdict of the Indonesian Mahkamah Konstitusi on the judicial review about the Law No. 1/PNPS/1965 on the eradication of blashphemy and defamation on religion has given perspective on the religious freedom and defamation of religion. It argues that the term ‘penodaan agama’ defined in the Indonesian Criminal Law is vague and has not clarified such relevant concepts as blashphemy, defamation of religion, and hatred speech. In fact, these three concepts are interchangeablely and chaotically used in this law. It also concludes that the Mahkamah Konstitusi has failed to take ‘middle way’ as to bridge and accommodate several interests retained in this legal attempt of judicial review and the Mahkamah Konstitusi takes not only constitutional but also political issues for its legal considerations, demonstrating that MK has obliviously revived the political ideology of ‘Piagam Jakarta’.